TAX ENGINEERING IN OFFSHORE FINANCIAL CENTERS AS AN INSTRUMENT OF SHADOWIZATION OF THE GLOBAL ECONOMY - REZNIKOVA, Natalia; IVASHCHENKO, Oksana; DVORNYK, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article reviews offshore financial centers from established to modern interpretations from the standpoint of their potential to influence the processes of shadowing the global economy. Considered "unfair location tax competition" as the reverse side of tax engineering in offshore financial centers. It has been established that to this day, both in the practice of BNP and exporting companies, such types of tax engineering with the participation of offshore financial centers have been used, such as: 1) tax planning (taking into account the possibilities of existing legislation); 2) tax evasion and money laundering (with tax evasion provided for by law); 3) the practice of tax arbitrage through hybrid mismatch and corporate tax games. The negative consequences of the development of offshore business for the world economy in the context of its shadowing in general and the international movement of capital, in particular, include: the outflow of capital from different groups of countries, destabilizing their economic development; money laundering and (in recent years) increased financing of terrorism; instability in the development of national economies due to the growth of money supply in developed countries; accumulation of capital, "not working" for the purpose of economic development; increased stock market volatility, volatility in tax and interest rates due to free cross-border migration of large amounts of financial resources; instability and fluctuations in demand for capital that does not correspond to the real situation in the world currency and financial markets; deterioration in investment ratings of individual countries and an increase in the burden on the balance of payments; leakage of investment resources that could be used to achieve the goals of economic development and growth; narrowing of the tax base and tax revenues to the budget; an increase in the cost of maintaining the security of the state (the fight against smuggling), which leads to a redistribution of finance in the economy; implementation of unreasonable macroeconomic, tax and monetary policies by individual countries due to a lack of understanding of the modern specifics of offshore business. It has been established that the use of an offshore company for export usually allows you to sell goods at extremely low prices, and then resell through an offshore company to the final buyer at market prices. The taxable profit of the national exporter in this case remains minimal, and the difference between the real and understated price for export forms the profit of an offshore company registered in a country with a preferential or zero income taxation level. It is noted that the traditional understanding of offshore centers will change, and new tax optimization tools will appear, such as the optimization of taxation of dividends, which will lead to the shadowing of the global economy.